Design and construction problems connected with ensuring even thermal insulation of single-layer walls = Konstrukcyjne i wykonawcze problemy związane z zapewnieniem równomiernej izolacyjności termicznej ścian jednowarstwowych - Stawiski, Bohdan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The design of single-layer walls appears to be extremely simple. In the opinion of many designers, the additional insulation of tie beams and balconies continues to solve all problems. However, tests on single-layer walls show that the expressed opinion is not valid. The study quotes the results of tests on single-layer walls with strong signs of freezing.
Keywords: ściany jednowarstwowe; ochrona cieplna; mostki termiczne; single-layer wall; thermal protection; thermal bridges; detection